IMPLEMENTASI SISTEM PENDATAAN SISWA BARU MENGGUNAKAN METODE AGILE - Rizki Aditiya; Aldis Sahputra (Journal of Research and Publication Innovation, 2025)
This internship report aims to document the implementation process of a student data collection system at the Baitul Yatim H. Caong Foundation using the Agile method. In today's digital era, efficient and accurate student data management is very important to support administrative activities and decision making. The Agile method was chosen because of its flexibility in dealing with changing needs and its ability to improve collaboration between the development team and stakeholders. This project began with a needs analysis involving the foundation to understand the existing data collection process. Furthermore, a system design was carried out that prioritized user experience and ease of access. Implementation was carried out in several iterations, where each iteration produced new features that were immediately tested and evaluated. The result of this implementation is an integrated student data collection system, allowing for faster and more accurate data management. From the evaluation results, this system has succeeded in increasing the efficiency of the data collection process and making it easier for foundation staff to access student information. This report is expected to be a reference for other institutions that want to implement a similar system and provide insight into the application of the Agile method in the development of educational information systems.